IMPROVING STUDENTS' INTEREST IN POETRY WRITING LEARNING BY USING EPIGONAL TECHNIQUE - Triyanto Triyanto; Sumarwati Sumarwati; Kundharu Saddhono (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2018)
This study aims to increase student interest in learning to write poetry with epigonal techniques on students of class VII E SMP Negeri 16 Surakarta academic year 2016/2017. This research is a Classroom Action Research (PTK). This research was started from January 2017-August 2017. Data collection techniques used were observation techniques, interviews, tests, field notes, and document analysis. Data analysis techniques used in this study are descriptive comparative and critical analysis. The results of this study are the application of epigonal techniques which can increase student learning interest in learning to write poetry in class VII E SMP Negeri 16 Surakarta Lesson Year 2016/2017. This is seen in cycle I meeting 1, the percentage of students who were active during apperception 75.17%; attention and concentration 75,86%; and students' enthusiasm and enthusiasm when teachers delivered materials of 78.62%. In the second cycle of meeting 2 there was an increase of the students who were active during the apperception was 84.83%; attention and concentration 86,21%; and students' enthusiasm and enthusiasm when teachers delivered material 86.20%.